Lukisan Sebagai Materi Animasi dalam Film “Aku, Trimah Perempuan Itu” - Dyah Arum Retnowati (Rekam: Jurnal Fotografi, Televisi, Animasi)
A film is one of the media that is able to deliver an event andmessage as well, not only ideologically but also structurally throughdiscontinuity principle. Film as a medium to reflect an event with manystyles according to its characteristics. This film is created to bring up aphenomenon that happened in society, using animation technique stressed to frame by frame recording technique, panning and zooming system that are combined with live action technique.It is such a concern when we watch, read and hear from the mediathat contain of news about murders of his/her own family members. Amother who killed her own child, a wife who mutilated her own husband.“Me, Trimah That Woman”is an illustration about a woman who experienced and did a murder on her own way, killed her children and herhusband. What kind of thoughts and how could this happen, that made awoman, a mother, a wife is able to do this kind of thing?The story that packaged in this film tries to revive a group of pictures to represent dream and imagination world of the actor in surrealism style, and used as an effort to deliver the message non verbally through meaningful symbols. The symbol is also used to replace the violence scenes and the effects on film as well. Those entirely aimed in order to  make this film to become a reflection, to grow the empathy, sympathy and also wisely understanding to judge an incident in this life.